Simultaneous Realization of Dynamic and Hybrid Multiplexed Holography via Light‐Activated Chiral Superstructures (Laser Photonics Rev. 16(5)/2022). Issue 5 (11th May 2022) - Chen, Peng; Shen, Zhi‐Xiong; Xu, Chun‐Ting; Zhang, Yi‐Heng; Ge, Shi‐Jun; Ma, Ling‐Ling; Hu, Wei; Lu, Yan‐Qing
Abstract : Dynamic Multiplexed Holography In article number 2200011, Peng Chen, Wei Hu, Yan‐Qing Lu, and colleagues from Nanjing University report a new strategy for simultaneous realization of dynamic and high‐dimensional multiplexed holography. Via light‐directed liquid‐crystalline chiral superstructures, a photo‐active, bidirectional, polarization‐ and time‐dependent hologram is demonstrated. This novel methodology integrates diverse multiplexing schemes into a single device, facilitating advanced display, security and communication.